Overview Polymorphism Gen LOX-1 3'UTR188C/T in Medan, Indonesia - Dr.dr Shahrul Rahman, Sp.PD., Finasim (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
LOX-1 belongs the subgroup of scavenger receptor class E. Until class E. Until now, there are 7 polymorphisms that hace been identified in the LOX-1 gene. One is 3'UTR188C/T. The serum LOX-1 levels were significantly higher in NAFLD patients than in healthy controls./